2005
DOI: 10.1139/g05-004
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a triplet repeat in a conifer

Abstract: The opportunity to trace the evolution of a triplet repeat is rare, especially for seed-plant lineages with a well-defined fossil record. Microsatellite PtTX2133 sequences from 18 species in 2 conifer genera were used to calibrate the birth of a CAGn repeat, from its protomicrosatellite origins to its repeat expansion. Birth occurred in the hard-pine genome ~ 136 million years ago, or 14 million generations ago, then expanded as a polymorphic triplet repeat 136-100 million years before a major North American v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Although the idea of an MS threshold has been investigated by numerous studies and approaches, a consensus on its existence, exact value(s), and differences across TRs of different motifs is yet to be reached (Jurka and Pethiyagoda 1995; Messier et al 1996; Bell and Jurka 1997; Cox and Mirkin 1997; Dechering et al 1998; Field and Wills 1998; Rose and Falush 1998; Dieringer and Schlotterer 2003; Lai and Sun 2003). Moreover, several studies offered evidence of slippage and slippage-like processes contributing to expansions and contractions of very STRs (Zhu et al 2000; Dieringer and Schlotterer 2003; Messer and Arndt 2007), which has led some investigators to question the very notion of an MS threshold (Pupko and Graur 1999; Noor et al 2001; Sokol and Williams 2005; Leclercq et al 2010). Although slippage does occur at very STRs, its rate at such repeats is extremely low (Kunkel 1990; Eckert et al 2002; Garcia-Diaz and Kunkel 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although the idea of an MS threshold has been investigated by numerous studies and approaches, a consensus on its existence, exact value(s), and differences across TRs of different motifs is yet to be reached (Jurka and Pethiyagoda 1995; Messier et al 1996; Bell and Jurka 1997; Cox and Mirkin 1997; Dechering et al 1998; Field and Wills 1998; Rose and Falush 1998; Dieringer and Schlotterer 2003; Lai and Sun 2003). Moreover, several studies offered evidence of slippage and slippage-like processes contributing to expansions and contractions of very STRs (Zhu et al 2000; Dieringer and Schlotterer 2003; Messer and Arndt 2007), which has led some investigators to question the very notion of an MS threshold (Pupko and Graur 1999; Noor et al 2001; Sokol and Williams 2005; Leclercq et al 2010). Although slippage does occur at very STRs, its rate at such repeats is extremely low (Kunkel 1990; Eckert et al 2002; Garcia-Diaz and Kunkel 2006).…”
Section: Introductionmentioning
confidence: 99%
“…From a molecular perspective, the threshold length would result from the minimum length of repeated sequences allowing stable misalignment and therefore DNA slippage. Other authors have proposed a more continuous version of this general model, suggesting that slippage occurs even at very short STRs, although at a reduced rate (Pupko and Graur 1999; Noor et al 2001; Sokol and Williams 2005). Under this scenario, there is no threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing homologous loci across related species with known evolutionary relationships, this approach has been extensively used to analyze the dynamics of long STRs (Richard and Dujon 1996; Angers and Bernatchez 1997; Dettman and Taylor 2004). The approach has also demonstrated that tandem duplications occur at STR loci shorter than eight nucleotides in swallows (Primmer and Ellegren 1998), fruit flies (Noor et al 2001), and conifers (Sokol and Williams 2005). These outcomes were interpreted as a result of DNA slippage.…”
Section: Introductionmentioning
confidence: 99%
“…Examining patterns of diversity for locus 11A4D, we can see stages in the ''life cycle'' of a microsatellite locus (Zhu et al 2000;Sokol and Williams 2005). Figure 5 illustrates changes in repeat number and the number of alleles along the divergences of species as inferred from the mtDNA phylogeny.…”
Section: Discussionmentioning
confidence: 99%
“…In part, this is because there is not yet consensus on the mechanisms that underlie the high degree of polymorphism seen at many microsatellite loci (Jarne and Lagoda 1996;Goldstein and Pollock 1997;Ellegren 2000;Schlo ¨tterer 2000). Although there have been a number of attempts to reconstruct phylogenies between closely related organisms using microsatellite loci (e.g., Roy et al 1994;Harr et al 1998;Petren et al 1999;Muir et al 2000;Ritz et al 2000;Uphyrkina et al 2001;Rout et al 2008), only a few studies have used data from wild species to investigate changes in microsatellite loci at the sequence level over evolutionary time (Ross et al 2003;Sokol and Williams 2005;Ochieng et al 2007).…”
mentioning
confidence: 99%